Factors influencing job performance among Administratvie Staff At Syarikat Air Melaka Berhad (SAMB) / Nur Atikah Hamzah and Nurul Jannah Zulkifli - Hamzah, Nur Atikah; Zulkifli, Nurul Jannah (Faculty of Administrative Science and Policy Studies, 2013)
The purpose of this study is to identify the factors influencing the job performance among the administrative staff. The study has been carried out at Syarikat Air Melaka Berhad (SAMB). It involved eight departments in SAMB which are department of information technology, department of audit, department of customer center and department of business development. The objectives of this research is to identify the relationship between motivation and job performance, the relationship between working experience and job performance and the relationship between knowlegde and skill towards the job performance among the administrative staff at Syarikat Air Melaka Berhad (SAMB). The convenient sampling technique has been used to select the respondent from the sampling frame of these eight departments in SAMB. The overall results of the data analysis suggest that knowledge and skills have high significant relationship towards the job performance among the administrative staff.